Independent Development Model for Village Land Asset Management In Segara Kodang by Sesetan Village - UTAMA, I Wayan Kartika Jaya; WIRYANI , Made (Protection: Journal Of Land And Environmental Law, 2023)
Efforts to improve the welfare and independence of Krama Desa Adat through increasing the role of traditional villages are very appropriate, especially in Bali. Based on the Regional Regulation of Bali Province Number 4 of 2019 concerning Customary Villages, Sesetan Traditional Village manages its land assets through the independence of indigenous village communities with the aim of forming a legal forum in the form of providing legal certainty for efforts to develop Small and Medium Enterprises in empowering customary village land assets. Based on the above, the main problems studied in this study can be formulated, namely: How to improve village land management to create multi-management to empower indigenous peoples' businesses to achieve independent customary villages. The method used in this study is the Empirical method. For the Development of Small and Medium Enterprises in the Legality of Land Asset Management, the Village uses the purpose of access reform conceptualized by Tri Hita Karana in managing access reform which aims to prosper indigenous peoples and relieve the community in carrying out these customs. Focusing on empowering access reform with the concept of Tri Hita Karana in preserving the surrounding environment.